School Cartography and Spatial Thinking of Brazilian Students at the end of Junior High School - Duarte, Ronaldo Goulart (Boletim Paulista de Geografia, 2018)
This paper was written under the assumption that the main purpose of keeping Geography in the K-12 curriculum is to foster the development of a particular kind of reasoning that can be called geographical. To achieve this goal, we strongly believe in the importance of School Cartography and the development of student’s Spatial Thinking. This mode of thinking has been consistently defined as a constructive amalgam of three elements: concepts of space, tools of representation, and processes of reasoning. Using such a framework we have administered the STAT (Spatial Thinking Ability Test) to 268 students of six different Brazilian schools in the state of Rio de Janeiro, all of them finishing their 9th grade. The results help us to diagnose how well Geography teaching in Brazilian schools is achieving the goal mentioned above. It may also help guide future strategies to overcome the pedagogical problems regarding the development of Spatial Thinking using Cartography and Geography in school.